Analisis Kebijakan Pendidikan dan Dampaknya Pada Motivasi dan Prestasi Akademik Siswa - Hanifah, Fathia; Munawwarah, Tarisa; Silalahi, Khairul Amri; Pras, Jogi; Darmansyah, T. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze the relationship between educational policies and student motivation and academic achievement. In this study, school principals as educational leaders play a central role in implementing policies that impact the welfare of students and teachers, as well as the learning environment. The research method used is a qualitative literature study, with a focus on policy analysis involving curriculum components, education funding, teacher development, and equitable access to education. The research results show that educational policies designed taking into account the social and economic context can increase student motivation and contribute to academic achievement. Reward-based policies, access to technology, and strengthening synergy between school principals, teachers and parents have proven effective in creating a conducive learning atmosphere.